Complexes of {W6I8}4+ Clusters with Carboxylates: Preparation, Electrochemistry, and Luminescence. Issue 35 (22nd September 2017) - Sokolov, Maxim N.; Brylev, Konstantin A.; Abramov, Pavel A.; Gallyamov, Marsel R.; Novozhilov, Igor N.; Kitamura, N.; Mikhaylov, Maxim A.
Abstract : The reactions between (Bu4 N)2 [W6 I8 I6 ] (1 ) and silver carboxylates RCOOAg in CH2 Cl2 afforded new luminescent carboxylate complexes (Bu4 N)2 [W6 I8 (RCOO)6 ] [R = CH3 (2 ), C6 H5 (3 ), C2 F5 (4 ), C3 F7 (5 ), C6 F5 (6 )]. The complexes were characterized by single‐crystal X‐ray diffraction, elemental analysis, cyclic voltammetry, and IR and NMR spectroscopy. Complexes1 –6 all exhibit intense and long‐lived photoluminescence. The carboxylate complexes undergo reversible electrochemical oxidation in two consecutive one‐electron steps. Abstract : Octahedral hexatungsten(II) iodide clusters [W6 I8 L8 ] 2– with a series of terminal aliphatic or aromatic carboxylate ligands are prepared. All of the complexes exhibit bright and long‐lived emission in CH3 CN with quantum yields and lifetimes of 0.39–0.54 and 20.3–42.2 µs, respectively. The redox, spectroscopic, and photophysical properties of [Mo6 I8 L6 ] 2– are modulated by the p K a value of RCOOH.